Emotion Dysregulation and Conspiracy Beliefs about COVID-19: The Moderating Role of Critical Social Media Use - Cristiano Scandurra; Rosa Pizzo; Luca Emanuel Pinto; Claudia Cafasso; Renata Pellegrini; Federica Cafaggi; Oriana D'Anna; Benedetta Muzii; Vincenzo Bochicchio; Nelson Mauro Maldonato (MDPI AG, 2022)
As COVID-19 has spread worldwide, conspiracy theories have proliferated rapidly on social media platforms, adversely affecting public health. For this reason, media literacy interventions have been highly recommended, although the impact of critical social media use on the development of COVID-19 conspiracy theories has not yet been empirically studied. Moreover, emotional dysregulation may play another crucial role in the development of such theories, as they are often associated with stress, anxiety, lack of control, and other negative emotions. Therefore, the aim of this study was to test the hypothesis that emotion dysregulation would be positively associated with conspiracy beliefs about COVID-19 and that critical use of social media would attenuate this association. Data from 930 Italian participants (339 men and 591 women) were collected online during the third wave of the COVID-19 outbreak. A moderated model was tested using the PROCESS Macro for SPSS. Results showed that: (1) emotion dysregulation and critical social media use accounted for a significant proportion of the variance in conspiracy beliefs about COVID-19; and (2) critical social media use moderated the effect of emotion dysregulation on conspiracy beliefs about COVID-19. Implications for preventing the spread of conspiracy theories are discussed.